Bitcoin is not the New Gold - A Comparison of Volatility, Correlation, and Portfolio Performance - Tony Klein; Hien Pham Thu; Thomas Walther (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
Cryptocurrencies such as Bitcoin are establishing themselves as an investment asset and are often named the New Gold. This study, however, shows that the two assets could barely be more dierent. Firstly, we analyze and compare conditional variance properties of Bitcoin and Gold as well as other assets and nd dierences in their structure. Secondly, we implement a BEKK-GARCH model to estimate time-varying conditional correlations. Gold plays an important role in nancial markets with ight-to-quality in times of market distress. Our results show that Bitcoin behaves as the exact opposite and it positively correlates with downward markets. Lastly, we analyze the properties of Bitcoin as portfolio component and nd no evidence for hedging capabilities. We conclude that Bitcoin and Gold feature fundamentally dierent properties as assets and linkages to equity markets. Our results hold for the broad cryptocurrency index CRIX. As of now, Bitcoin does not reect any distinctive properties of Gold other than asymmetric response in variance.
Keywords: C10; C58; G11; 330; BEKK; Bitcoin; CRIX; Cryptocurrency; Gold; GARCH; Conditional Correlation; Asymmetry; Long memory